Linking Sources of Consumer Confusion to Decision Satisfaction: The Role of Choice Goals. Issue 4 (25th February 2013) - Wang, Qing; Shukla, Paurav
ABSTRACT Previous empirical research on the relationship between consumer confusion and customer satisfaction has largely neglected the role of choice goals. In a context of technologically complex products, the authors analyze the effect of selected choice goals on the consumer confusion‐decision satisfaction link. The empirical findings, which are based on a field study of smart phone users, show that different sources of confusion have distinctive effects on choice goals, which in turn influence decision satisfaction. For example, while confusion caused by ambiguous information and choice overload is found to reduce choice confidence, perceived attribute similarity between products or brands increases choice confidence. Among the choice goals, evaluation costs and negative affect are found to increase decision satisfaction. The findings have important implications for marketers and consumer policymakers in terms of marketing communication and customer satisfaction.